2017
DOI: 10.1167/iovs.17-21525
|View full text |Cite
|
Sign up to set email alerts
|

Visual Impairment, Undercorrected Refractive Errors, and Activity Limitations in Older Adults: Findings From the Three-City Alienor Study

Abstract: About one-sixth of IADL limitations and one-fifth of social participation restrictions could be prevented by an optimal optical correction. These results underline the importance of eye examinations in older adults to prevent disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Many prior studies have taken a less nuanced approach to understanding the adverse consequences of VI. For example, among the numerous studies that have reported increased activity limitations in older adults with VI (11,33,34), few have accounted for whether respondents successfully accommodate for declines in functioning, perform activities less frequently, or perform an activity only with considerable difficulty. In the current study, the activity limitation hierarchies were a significant mediator of the relationship between VI and SWB, which suggests that interventions to promote successful accommodation could move individuals higher on these hierarchies, which may improve SWB.…”
Section: Discussionmentioning
confidence: 99%
“…Many prior studies have taken a less nuanced approach to understanding the adverse consequences of VI. For example, among the numerous studies that have reported increased activity limitations in older adults with VI (11,33,34), few have accounted for whether respondents successfully accommodate for declines in functioning, perform activities less frequently, or perform an activity only with considerable difficulty. In the current study, the activity limitation hierarchies were a significant mediator of the relationship between VI and SWB, which suggests that interventions to promote successful accommodation could move individuals higher on these hierarchies, which may improve SWB.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there are treatment options for the majority of these diseases, nevertheless there is still a sizeable number of subjects with moderate and severe VI (presenting visual acuity <6/18, but ≥3/60 in the better eye), namely, 1.0% in high-income countries (Central Europe, Western Europe, North America, Australasia, Pacific Asia) in 2010 (point prevalence) ( 4 ). Decreased vision does not only reduce mobility but also limits activity of daily life and restricts social participation ( 5 ); similar impairments are also seen in subjects with depression.…”
Section: Introductionmentioning
confidence: 98%
“…According to a study by Nael et al [21] Myopia is a very common ophthalmologic disease, and its prevalence is increasing worldwide. Considering educational activities, continuous urbanization, and westernization, it is estimated that the prevalence of myopia will continue to increase [27] [28].…”
Section: Discussionmentioning
confidence: 99%